Bioethical education: an analytical review of its rationale and challenges - Hashi, Abdurezak Abdulahi (2015)
Bioethics forms an intersection between life sciences, law, moral philosophy and social sciences. It is driven by the motive of balancing between progress in biosciences, the safety of living organism including human beings and the protection of the natural environment and its resources. This paper uses analytical approach, and aims to review the rationale and modern challenges of bioethical education.